Predictive Value of the CHA2DS2-VASc Score for Mortality in Hospitalized Acute Coronary Syndrome Patients With Chronic Kidney Disease - Wu, Yaxin; Gao, Yanxiang; Li, Qing; Wu, Chao; Xie, Enmin; Tu, Yimin; Guo, Ziyu; Ye, Zixiang; Li, Peizhao; Li, Yike; Yu, Xiaozhai; Ren, Jingyi; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Chronic kidney disease (CKD) patients have a high prevalence of coronary artery disease and a high risk of cardiovascular events. The present study assessed the value of the CHA2DS2-VASc score for predicting mortality among hospitalized acute coronary syndrome (ACS) patients with CKD. Methods: This was a retrospective cohort study that included CKD patients who were hospitalized for ACS from January 2015 to May 2020. The CHA2DS2-VASc score for each eligible patient was determined. Patients were stratified into two groups according to CHA2DS2-VASc score: < 6 (low) and ≥ 6 (high). The primary endpoint was all-cause mortality. Results: A total of 313 eligible patients were included in the study, with a mean CHA2DS2-VASC score of 4.55 ± 1.68. A total of 220 and 93 patients were assigned to the low and high CHA2DS2-VASc score groups, respectively. The most common reason for hospitalization was unstable angina (39.3%), followed by non-ST-elevation myocardial infarction (35.8%) and ST-elevation myocardial infarction (24.9%). A total of 67.7% of the patients (212/313) received coronary reperfusion therapy during hospitalization. The median follow-up time was 23.0 months (interquartile range: 12-38 months). A total of 94 patients (30.0%) died during follow-up. The high score group had a higher mortality rate than the low score group (46.2% vs. 23.2%, respectively; p < 0.001). The cumulative incidence of all-cause death was higher in the high score group than in the low score group (Log-rank test, p < 0.001). Multivariate Cox regression analysis indicated that CHA2DS2-VASc scores were positively associated with all-cause mortality (hazard ratio: 2.02, 95% confidence interval: 1.26-3.27, p < 0.001). Conclusion: The CHA2DS2-VASc score is an independent predictive factor for all-cause death in CKD patients who are hospitalized with ACS. The simple and practical scoring system can be used for the early identification of patients with a high risk of death.